AN ANALYSIS FROM THE PERSPECTIVE OF BIOMECHANICS AND KINESIOLOGY OF A MECHANICAL FUNCTIONAL ORTHESIS FOR SPINAL INJURY LEVEL C6 AND C7 - Costa da Silva, Estéfane; Lopes Rodrigues Neto, Jorge; Clay Fares dos Santos Júnior, Helder; Lopes Rodrigues Júnior, Jorge (Health and Society, 2021)
The spinal cord injury is characterized by damage to the spinal canal, which causes various complications in the individual’s life, whether physical, psychological and / or social. The incorporation of Assistive Technology consists of one of the forms of care and of increasing the quality of life of people with severe disabilities, such as quadriplegia. In the present study, there is the presentation of the mechanical functional orthosis for tetraplegic spinal cord injury level C6 and C7, triggered by the contraction of the extensor muscles of the wrist, flexors or extensors of the elbow, kinesiological functions compatible with the remaining functions observed in dermatomes. Understanding the important effects of spinal cord injury on affected patients, it is considered that the use of resources and products that aim to maintain, restore and / or maximize functionality is a primary factor for improving occupational performance. With this in mind, the orthosis presented in this work corroborates this scope, being a unique factor for engagement and return in the performance of activities of daily living, in addition to assisting in the rehabilitation process of these people.